PROGRAM PELATIHAN PENGEMBANGAN KOMPETENSI GURU SEKOLAH INKLUSI DI SDN KARAWACI 3 TANGERANG - Yunita, Intan; Jessica, Madeline; Utami, Sylvia Dwi; handayani, penny (Jurnal Bakti Masyarakat Indonesia, 2024)
SDN 3 Karawaci Tangerang is one of the schools designated as an inclusive school. Based on the results of the needs analysis conducted using observation, study of school documents, interviews, and FGDs with teachers, principals, education personnel, students, and parents, it was found that one of the main challenges at SDN Karawaci 3 is the unpreparedness in accommodating the needs of students with disabilities in inclusive schools. This main problem is caused by dif iculties in identifying students with disabilities in the classroom, teachers' lack of competence in teaching students with disabilities, inadequate facilities to accommodate students with disabilities, inef ective communication within the school ecosystem and a lack of discipline consistently applied by the school.. The training program provided aims to improve teachers' competence in teaching in inclusive schools, with the theme "Introduction to Characteristics, How to Communicate, and Learning Programs for Students with Special Needs".. The implementation of this training consists of three main sessions, namely Session I discusses the characteristics of students with disabilities in inclusive schools, Session II discusses ef ective communication strategies between teachers and the school ecosystem, and Session III discusses how to prepare an Individual Learning Program (IEP). The training evaluation was reviewed from two aspects, namely evaluation of training activities and evaluation of the achievement of objectives. In evaluating the achievement of objectives, the facilitator team looked at the achievement of objectives for each session based on participants' responses during discussions and the pre-test and post-test results. As a result, some participants experienced an increase in the average score on the post-test in each session, although the results were not significant. ABSTRAK: SDN 3 Karawaci Tangerang adalah salah satu sekolah dasar yang mendapatkan penunjukan sebagai sekolah inklusi. Berdasarkan hasil needs analisis yang dilakukan dengan metode observasi studi dokumen sekolah, wawancara, dan FGD kepada guru, kepala sekolah, tenaga kependidikan, siswa dan orangtua siswa, ditemukan bahwa salah satu tantangan utama di SDN Karawaci 3 ialah ketidaksiapan dalam mengakomodasi kebutuhan peserta didik berkebutuhan khusus (PDBK) di sekolah inklusi. Masalah utama ini disebabkan oleh kesulitan identifikasi PDBK di dalam kelas, kurangnya kompetensi guru dalam mengajar PDBK, fasilitas yang kurang memadai untuk mengakomodasi PDBK, komunikasi yang tidak efektif di dalam ekosistem sekolah, dan kedisiplinan yang kurang diterapkan secara konsisten oleh sekolah. Program pelatihan yang diberikan bertujuan untuk meningkatkan kompetensi guru dalam mengajar di sekolah inklusi, dengan tema “Pengenalan Karakteristik, Cara Berkomunikasi, dan Program Pembelajaran untuk Siswa Berkebutuhan Khusus”. Adapun pelaksanaan pelatihan ini terdiri dari tiga sesi utama yaitu Sesi I membahas mengenai karakteristik PDBK di sekolah Inklusi, Sesi II membahas mengenai strategi Komunikasi yang efektif antara Guru dengan Ekosistem Sekolah, dan Sesi III membahas mengenai cara penyusunan Program Pembelajaran Individual (PPI). Evaluasi terhadap pelatihan ditinjau dari dua aspek, yaitu evaluasi kegiatan pelatihan dan evaluasi pencapaian tujuan. Dalam evaluasi pencapaian tujuan, tim fasilitator melihat pencapaian tujuan setiap sesi berdasarkan tanggapan peserta saat berdiskusi, dan hasil dari pre-test serta post-test. Hasilnya beberapa peserta mengalami peningkatan rata-rata skor pada post test dalam setiap sesi, walaupun hasilnya belum signifikan.